A Blueprint for a Better Digital Society - Lanier, Jaron; Weyl, E. Glen (Harvard Business Review, 2018)
Digital transformation is remaking the human world, but few are satisfied with how that’s been going. That’s especially true in media, where the dominant model of targeted advertising derived from data surveillance and used to fund free-to-the-public services like social media and search is increasingly viewed as unsustainable and undesirable.